UJI BERBAGAI MACAM PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI - WIYONO, WIYONO; AZIEZ, ACHMAD FATCHUL (JURNAL ILMIAH AGRINECA)
The object of reseacch was the effect kind of liquid organic fertilizers and the kind concentration to the grown and yield of rice plant.